The Effectiveness of Sexual Satisfaction Training and the Masters and Johnson Approach on Marital Adjustment and Conflict in Couples with Sexual Dissatisfaction - Rasouli, Samiraalsadat; Golparvar, Mohsen; Ramezani, Mohammad Arash; Hasani, Jafar (Applied Family Therapy Journal (AFTJ), 2021)
Aim: The present study aimed to determine the effectiveness of Iranian sexual satisfaction training and the Masters and Johnson approach on marital adjustment and conflict. Methods: The research method was three-group quasi-experimental at three stages of pre-test, post-test, and a two-month follow-up. Among 60 couples, who visited two Centers for Psychology and Counseling in Tehran in winter 2018, we selected 45 couples by the purposive method and assigned them to two experimental groups and a control group (15 per group). We used the Marital Conflict Questionnaire (Sanaei et al., 2007), and the Dyadic Adjustment Scale (Spanier, 1976) at the pre-test, post-test, and follow-up stages. The two groups of the Iranian sexual satisfaction training and the Masters and Johnson approach training were trained in 6 sessions. We analyzed data by mixed analysis of variance with repeated measures and Bonferroni post hoc test. Results: The results indicated significant differences between the Iranian sexual satisfaction group with the control group in the marital adjustment (p < 0.01), and the Iranian sexual satisfaction training group with the Masters and Johnson approach group as well as the control group in marital conflict (p < 0.05). There was a significant difference only in the marital conflict between the Masters and Johnson training group with the control group (p < 0.05). Conclusion: The sexual satisfaction Iranian training was effective in reducing conflict and increasing adjustment, and the Masters and Johnson approach was effective in reducing marital conflicts.